2015
DOI: 10.1158/0008-5472.can-15-0291
|View full text |Cite
|
Sign up to set email alerts
|

An Imbalance in TAZ and YAP Expression in Hepatocellular Carcinoma Confers Cancer Stem Cell–like Behaviors Contributing to Disease Progression

Abstract: Transcriptional coactivator with PDZ-binding motif (TAZ) and yes-associated protein (YAP) are equivalently placed downstream effectors of the Hippo pathway with oncogenic roles in human cancers. However, the expression profiles of TAZ/YAP differ depending on the cancer cell type, suggesting that these proteins have different roles during cancer progression, yet no studies have examined the biologic significance of the balance between TAZ and YAP expression levels. Here we examined the functional roles of TAZ/Y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
93
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 33 publications
(37 reference statements)
7
93
0
1
Order By: Relevance
“…52 In hepatocellular carcinoma, TAZ is predominantly expressed under normal conditions, but a switch into YAP-dominant expression is thought to be a key step to acquire a cancer stem-like property. 53 Moreover, YAP-and TAZdeficient mice show different phenotypes: YAP-deficient mice are embryonic lethal, whereas TAZ knockout mice are viable. [54][55][56] The differential functions of YAP and TAZ can be explained by the differential binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…52 In hepatocellular carcinoma, TAZ is predominantly expressed under normal conditions, but a switch into YAP-dominant expression is thought to be a key step to acquire a cancer stem-like property. 53 Moreover, YAP-and TAZdeficient mice show different phenotypes: YAP-deficient mice are embryonic lethal, whereas TAZ knockout mice are viable. [54][55][56] The differential functions of YAP and TAZ can be explained by the differential binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…In the same sample collection, nonetheless, YAP overexpression was associated with HCC poor prognosis, and a compensatory YAP upregulation following TAZ depletion conferred cancer stem cell-like properties to HCC cells [18]. …”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the phosphorylation of YAP results in its cytoplasmic retention and reduced nuclear YAP and transcriptional activity of TEA domain family (14)(15)(16). Therefore, RT-qPCR was performed in order to analyze the expression of CTGF and CYR61, two well-characterized YAP target genes (18,19), in SMMC-7721 cells MOB2 overexpressing-cells, MOB2 knockout cells and their corresponding vector control cells. It was revealed that the overexpression of MOB2 significantly decreased the expression of CTGF and CYR61, while the knockout of MOB2 significantly promoted the transcription of CTGF and CYR61 compared with the levels in their corresponding vector control cells (P<0.05; Fig.…”
Section: Mob2-induced Yap Phosphorylation Is Independent Of Ndr1/2 Acmentioning
confidence: 99%